1946
DOI: 10.1037/h0055013
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of socioeconomic status to personality inventory and achievement test scores.

Abstract: One of the fundamental problems of sociology and social psychology is to determine the effect of various social conditions on the personalities of the members of a society. The impress of social variables upon the individual can be observed and classified from a number of different aspects. One of the most important of these, especially in a mobile, industrial, and stratified society, is socio-economic status. It is the purpose of this paper to consider the relationship of socio-economic status to achievement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1948
1948
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…5 to VIII in a war-boom community. Gough (58) found only a slight positive correlation between socio-economic status and achievement, after IQ had been partialled out, among 127 sixth-grade pupils. Lobaugh (78) found that girls averaged somewhat higher on marks, while boys averaged somewhat higher on achievement tests; insufficient data were presented to evaluate the reliability or relative importance of the differences involved.…”
Section: Interpretation Of Test Scoresmentioning
confidence: 94%
“…5 to VIII in a war-boom community. Gough (58) found only a slight positive correlation between socio-economic status and achievement, after IQ had been partialled out, among 127 sixth-grade pupils. Lobaugh (78) found that girls averaged somewhat higher on marks, while boys averaged somewhat higher on achievement tests; insufficient data were presented to evaluate the reliability or relative importance of the differences involved.…”
Section: Interpretation Of Test Scoresmentioning
confidence: 94%
“…Both intraversion and neuroticism in various senses have been attributed to those who do well academically (Gough 1946(Gough , 1949Vernon 1939 ; MacQuarry 1953) ; in some societies, of course, intraversion may well be more synonymous with social abnormality and so with neuroticism than it is in others. To sum up, there is little doubt that anxiety, in some sense of that word, contributes to rapid conditioning and to good academic achievement.…”
Section: And Communicationmentioning
confidence: 99%
“…The relationship between social status and intelligence and achievement has been emphasized in these studies (7,14). Other studies have involved personality (2,6), extracurricular activities (9,15), social acceptance (1,11), honors received (1), attitudes (8,10), and morale (3). Results usually indicate that upper status pupils exceed lower status pupils on achievement and intelligence test scores, marks in school, adequacy of adjustment, number of activities, social relationships, and attitudes toward school.…”
mentioning
confidence: 99%